The effect of transformational leadership style, employee creativity, and employee empowerment on employee performance at PT Casa Woodworking Industry - Togar Naibaho; Winfrontstein Naibaho (Enrichment : Journal of Management, 2023)
Every business or business is required to be able to continue to develop to face every opportunity and threat that comes from competition between business organizations. a business organization is required to have the right strategy that can help the business or business survive and have an advantage compared to competing businesses or businesses. Along with the increasingly uncertain and complex business environment that results in changes to the market and consumer needs, it requires businesses to be able to find strategies that can create products that match market demands. Employee performance is a parameter for measuring the performance of a business. Employee performance is often interpreted as the output of all business activities, both individual and group in nature, which have an impact on business continuity and sustainability. In the development of organizational behavior, the level of creativity possessed by an employee can also be formed from patterns of interaction that occur in the work environment and can further form collective creativity. Employee creativity/employee creativity has a significant influence on employee performance. Transformational leadership has a significant influence on employee performance. Employee Empowerment/Employee Empowerment does not have a significant effect on employee performance.